Supplement A to Chippewa/Ojibwa/Anishinabe and Selected Related Works - Roufs, Timothy G (University of Minnesota, Duluth, 1984)
The "Working Bibliography of Chippewa/Ojibwa/Anishinabe and Selected Related Works" can be found by clicking the link under "Related to" in this record.